Beauty Standard Portrayed in The Princess Who Wasn't by Templeton Moss (PANOPTICON: Journal of English Studies, 2024)
This study has the purpose of deeply and critically analyzing the beauty myth standard, which is the major issue in the picture book entitled The Princess Who Wasn't that is mostly read by children. Beauty standards refer to the norms within a society that idealize specific physical traits and appearances. These standards may vary across different cultures and time periods, but they have a significant influence on an individual's self-perception and body image. With the fundamental theory of Beauty Myth by Naomi Wolf in 1990, this study adopts a qualitative methodology as the approach. By analyzing the narrative and visual representation, the study explores how the picture book presents beauty standards and their potential impact on young readers. Furthermore, the study examines the storyline of a picture book to determine whether it focuses more on changing someone's appearance or on emphasizing the significance of inner beauty and individuality. Beauty is becoming an oppression for women in society. The standard of beauty in society makes it necessary for a woman to look pretty, wear a dress, and be a beautiful woman. This analysis deeply examines beauty myths in society, the standard of beauty, and a woman's right to be herself.